2011
DOI: 10.3346/jkms.2011.26.9.1132
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Interleukin-33 (IL-33) and IL-33 Receptors (sST2 and ST2L) in Patients with Rheumatoid Arthritis

Abstract: The interleukin-33 (IL-33)/ST2 pathway has emerged as an intercellular signaling system that participates in antigen-allergen response, autoimmunity and fibrosis. It has been suggested that IL-33/ST2 signaling has been involved in the pathogenesis of rheumatoid arthritis (RA), because IL-33 and its receptor have been specifically mapped to RA synovium. The aim of this study was to determine the levels of IL-33 and sST2 in sera and synovial fluids in patients with RA. The serum level of IL-33 was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 29 publications
4
74
1
5
Order By: Relevance
“…Therefore, data from animal models do not provide univocal evidence. In RA patients, IL-33 serum levels are increased compared to normal and disease controls (OA and psoriatic arthritis (PsA)) [21][22][23][24]. Evidence from RA SF is conflicting as IL-33 was found to be either increased [25] or comparable [23] to OA SF.…”
Section: New Members Of Il-1 Family Il-33mentioning
confidence: 98%
“…Therefore, data from animal models do not provide univocal evidence. In RA patients, IL-33 serum levels are increased compared to normal and disease controls (OA and psoriatic arthritis (PsA)) [21][22][23][24]. Evidence from RA SF is conflicting as IL-33 was found to be either increased [25] or comparable [23] to OA SF.…”
Section: New Members Of Il-1 Family Il-33mentioning
confidence: 98%
“…A previous study revealed that serum IL-33 levels were elevated in sera and synovial fluid samples from patients with rheumatoid arthritis (RA), and the levels correlated with disease activity [29][30][31][32][33][34][35][36][37]. IL-33 is produced mainly in inflamed joints [29].…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that differences in the IL-33 levels of local synovial tissues from RA patients may exacerbate inflammation in RA patients. Indeed, the IL-33 levels in sera and synovial fluids are significantly higher than those in normal subjects or OA patients [1,2]. …”
Section: Discussionmentioning
confidence: 99%
“…Aside from tumor necrosis factor alpha (TNF-α) and interleukin (IL)-6, IL-33 is reportedly an important cytokine in the pathogenesis of RA. IL-33 levels in the serum and synovial fluids from RA patients are significantly higher than in samples from patients with osteoarthritis (OA) or normal subjects [1,2]. Xu et al [3 ]demonstrated that IL-33 treatment exacerbates K/BxN-induced arthritis in mice, and ST2 knockout mice developed attenuated arthritis induced by K/BxN sera.…”
Section: Introductionmentioning
confidence: 99%